Collaborative process mapping to improve work instructions and standardized work - Abreu, M. Florentina (2017)
Nowadays, companies are searching for models that are able to increase their performance, efficiency and competitiveness. Therefore, it is crucial to identify the current company status and its needs, adopting a suitable model for this. Many times, the success key consists in the adoption of tailor-made models developed by each organization. The company under study has developed a process mapping tool, called Value Stream Design in Indirect Areas (VSDiA) that has been used to map and improve its business processes, in this case, applied to Work Instructions and Standard Work creation. The adoption of this model has allowed the identification of weaknesses, strengths and improvement opportunities in the abovementioned processes, through a collaborative process team work. Furthermore, this tool has provided an overview about the whole process by all involved, as well as, increased transparency and accuracy of the current process and a vision for the future process.